Use of Pesticides By Gezira Vegetable Growers and Workers and The Alleged Health Effects - Elhassan, Abdelelah Mohammed (Gezira Journal of Health Sciences; Vol 3 No 1 (2007), 2007)
The main objective of this study is to investigate and establish the relationship between some socio-cultural and work conditions of pesticides use and some human health problems. Field visits were conducted as survey methods. Ninety vegetable tenants or agricultural workers were randomly taken from four villages, dispersed over three regions in the Gezira Scheme, where such villages are traditionally known for their engagement in vegetable production. A questionnaire covering some work conditions of pesticides use and some areas of human healthy problems, was developed as a tool to collect the required data. The collected data was analyzed using the analytical aid programme (SPSS). The chi-square tests were used to measure the level of significance. A confidence level of 0.05 was adopted as significant for all analyses performed. The major findings of the study were the following: The test of significance showed that there was insignificant association between the acute pesticides poisoning and the skin diseases risk. The test of significance showed that there was a significant association between the use of protective measures, the method of pesticides application and the personal hygiene.   الخلاصة:             هدفت هذه الدراسة بشكل رئيسي إلى إيجاد العلاقة بين بعض الظروف الثقافية – الاجتماعية مع بعض ظروف العمل المصاحبة لاستخدامات مبيدات الآفات الزراعية وبين بعض المشاكل الصحية للعاملين في هذا المجال. وقد توجهت الدراسة نحو تقييم هذه الظروف الثقافية – الاجتماعية وظروف العمل المصاحبة لاستخدامات المبيدات بهدف تحديد المشاكل الصحية التي سوف تنتج عن هذه الظروف وسط المزارعين.             ولقد تم القيام بزيارات ميداينة كوسيلة لهذه الدراسة ومن ثم تم اختيار عشوائي لعدد 90من مزارعي الخضر في أربع قرى في ثلاثة من أقسام مشروع الجزيرة ولتحقيق أهداف الدراسة فقد تم تصميم استبيان غطى بعض الظروف الثقافية – الاجتماعية وبعض ظروف العمل المصاحبة لاستخدام المبيدات إضافة لبعض المشاكل الصحية المتعلقة باستخدام هذه المبيدات. بعد جمع المعلومات المطلوبة تم تحليلها باستخدام الاختبار الإحصائي (مربع كاي) لقياس مستوى الدلالة حيث تم تحديد مستوى دلالي عند 0.05 لكافة التحليلات التي أجريت ولقد خلصت الدراسة للنتائج التالية: أوضح اختبار الدلالة عدم وجود علاقة بين الوعي بالمخاطر الصحية المصاحبة لاستخدام المبيدات وبين كل من تسمم المبيدات الحاد ومخاطر الإصابة بالأمراض الجلدية – كشف اختبار الدلالة عن وجود علاقة أو ارتباط بين استخدام الإجراءات الوقائية وطريقة رش المبيدات والنظافة الشخصية وبين كل من تسمم المبيدات الحاد ومخاطر الإصابة بالأمراض الجلدية وعلى ضوء هذه النتائج أقترحت بعض التوصيات.